Alteration in binocular fusion modifies audiovisual integration in children - Quercia P; Pozzo T; Marino A; Guillemant AL; Cappe C; Gueugneau N (Clinical Ophthalmology, 2019)
P Quercia,1 T Pozzo,2 A Marino,3 AL Guillemant,1 C Cappe,4 N Gueugneau11INSERM Unit 1093, Cognition-Action-Plasticité Sensorimotrice, University of Burgundy-Franche Comté, Dijon 21078, France; 2IIT@UniFe Center for Translational Neurophysiology, Istituto Italiano di Tecnologia, Ferrara, Italy; 3Private office, Vicenza 36100, Italy; 4Brain and Cognition Research Center, CerCo, Toulouse, FranceBackground: In the field of multisensory integration, vision is generally thought to dominate audiovisual interactions, at least in spatial tasks, but the role of binocular fusion in audiovisual integration has not yet been studied.Methods: Using the Maddox test, a classical ophthalmological test used to subjectively detect a latent unilateral eye deviation, we checked whether an alteration in binocular vision in young patients would be able to change audiovisual integration. The study was performed on a group of ten children (five males and five females aged 11.3±1.6 years) with normal binocular vision, and revealed a visual phenomenon consisting of stochastic disappearanceof part of a visual scene caused by auditory stimulation.Results: Indeed, during the Maddox test, brief sounds induced transient visual scotomas (VSs) in the visual field of the eye in front of where the Maddox rod was placed. We found a significant correlation between the modification of binocular vision and VS occurrence. No significant difference was detected in the percentage or location of VS occurrence between the right and left eye using the Maddox rod test orbetween sound frequencies.Conclusion: The results indicate a specific role of the oculomotor system in audiovisual integration in children. This convenient protocol may also have significant interest for clinical investigations of developmental pathologies where relationships between vision and hearing are specifically affected.Keywords: multisensory integration, binocular vision, audiovisual development, visual losses, ocular proprioception